Enhancement of Mechanical Properties on Aluminum 5052- H32 sheet for Automotive Panel Material using Various Coating Methods - Rifky Maulana Yusron; Hidayat Hidayat; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Aluminum alloy 5052-H32 sheet was applied widely in automotive industries, especially for body panel, trunk lid, door, roof, fender and bonnet. It was had numerous advantages such as excellent particular strength, high density, machinability, manufacturing method, high electrical conductivity and availability in various applications. The aims of this research is to provide optimum setting laminate oxide layer on the surface of Aluminum alloy sheet 5052-H32, also to analyze the microstructure and mechanical properties of deposited coatings as well as to compare the performance of anodization and plasma electrolytic oxidation coating in Aluminum alloy 5052-H32 sheet. Factorial L 2x3 was applied as design experiment. Which is current parameter had 2 levels; 200 and 250 minutes. Parameter Coating duration had 3 levels 15, 20, 30 minutes. The oxide layer coating is seen by conducting surface characterization. The improvement of surface hardness by micro-hardness test from 35.3 VHN to 65.8 VHN for anodizing coating, and plasma electrolytic oxidation coating is in the average of 67.9 VHN. The mechanical properties for surface hardness and adhesion strength of aluminum oxide coated of Aluminum alloy sheet 5052-H32 improved.